Distribution of PACAP and PAC1 Receptor in the Human Eye - Evelin Patko; Edina Szabo; Denes Toth; Tamas Tornoczky; Inez Bosnyak; Alexandra Vaczy; Tamas Atlasz; Dora Reglodi (Journal of Molecular Neuroscience, 2022)
Pituitary adenylate cyclase–activating polypeptide (PACAP) is a neuropeptide with widespread distribution and diverse biological functions. Several studies show that PACAP has strong cytoprotective effects mediated mostly through its specific PAC1 receptor (PAC1-R) and it plays important roles in several pathological conditions. Its distribution and altered expression are known in various human tissues, but there is no descriptive data about PACAP and its receptors in the human eyebulb. Since PACAP38 is the dominant form of the naturally occurring PACAP, our aim was to investigate the distribution of PACAP38-like immunoreactivity in the human eye and to describe the presence of PAC1-R. Semiquantitative evaluation was performed after routine histology and immunohistochemical labeling on human eye sections. Our results showed high level of immunopositivity in the corneal epithelium and endothelium. Within the vascular layer, the iris and the ciliary body had strong immunopositivity for both PACAP and PAC1-R. Several layers of the retina showed immunoreactivity for PACAP and PAC1-R, but the ganglion cell layer had a special pattern in the immunolabeling. Labeling was observed in the neuropil within the optic nerve in both cases and glial cells displayed immunoreactivity for PAC1-R. In summary, our study indicates the widespread occurrence of PACAP and its specific receptor in the human eye, implying that the results from in vitro and animal studies have translational value and most probably are also present in the human eye.

Effects of pituitary adenylate cyclase activating polypeptide (PACAP) in corneal epithelial regeneration and signal transduction in rats - Peter Kiss; Jozsef Farkas; Krisztina Kovacs; Valeria Gaal; Zsolt Biro; Aliz Szabo; Tamas Atlasz; Inez Bosnyak; Gabor Toth; Andrea Tamas; Dora Reglodi (International Journal of Peptide Research and Therapeutics, 2022)
Corneal epithelium responds to insults with a rapid wound healing, which is essential for maintaining vision. The proper balance of apoptotic and proliferation-stimulating pathways is critical for normal regeneration. Pituitary adenylate cyclase activating polypeptide (PACAP) is an important growth factor during the development of the nervous system and exerts cytoprotective effects in injuries. The aim of the present study was to investigate the effects of PACAP on corneal epithelial wound healing in rats and on two important protective signaling molecules, Akt and ERK1/2, both of which have been reported to play important roles during cell survival and regeneration, including corneal wound healing. Wistar rats received PACAP treatment in form of eyedrops, containing 1, 5 and 10 µg PACAP27, immediately and every two hours after corneal abrasion. Corneas were stained with fluorescein dye and further processed for histological staining or Western blot analysis for Akt and ERK1/2 expression. Our results showed that topical PACAP application enhanced corneal wound healing, as the area of injury was significantly less in PACAP-treated groups. Furthermore, both ERK1/2 and Akt signaling was induced upon PACAP administration in both injured and intact corneas. In summary, the present results show that PACAP enhances corneal wound healing in a rat model of corneal abrasion.

The Protective Effects of Endogenous PACAP in Oxygen-Induced Retinopathy - Timea Kvarik; Dora Reglodi; Dora Werling; Alexandra Vaczy; Petra Kovari; Edina Szabo; Krisztina Kovacs; Hitoshi Hashimoto; Tibor Ertl; Judit Gyarmati; Tamas Atlasz (Journal of Molecular Neuroscience, 2021)
Pituitary adenylate cyclase–activating polypeptide (PACAP) is a neuropeptide having trophic and protective functions in neural tissues, including the retina. Previously, we have shown that intravitreal PACAP administration can maintain retinal structure in the animal model of retinopathy of prematurity (ROP). The purpose of this study is to examine the development of ROP in PACAP-deficient and wild-type mice to reveal the function of endogenous PACAP. Wild-type and PACAP-knockout (KO) mouse pups at postnatal day (PD) 7 were maintained at 75% oxygen for 5 consecutive days then returned to room air on PD12 to develop oxygen-induced retinopathy (OIR). On PD15, animals underwent electroretinography (ERG) to assess visual function. On PD16, eyes were harvested for either immunohistochemistry to determine the percentage of the central avascular retinal area or molecular analysis to assess angiogenesis proteins by array kit and anti-apoptotic protein kinase B (Akt) change by western blot. Retinas of PACAP-deficient OIR mice showed a greater central avascular area than that of the wild types. ERG revealed significantly decreased b-wave amplitude in PACAP KO compared to their controls. Several angiogenic proteins were upregulated due to OIR, and 11 different proteins markedly increased in PACAP-deficient mice, whereas western blot analysis revealed a reduction in Akt phosphorylation, suggesting an advanced cell death in the lack of PACAP. This is the first study to examine the endogenous effect of PACAP in the OIR model. Previously, we have shown the beneficial effect of exogenous local PACAP treatment in the rat OIR model. Together with the present findings, we suggest that PACAP could be a novel retinoprotective agent in ROP.

Stability Test of PACAP in Eye Drops - Anita K. Kovacs; Tamas Atlasz; Dora Werling; Edina Szabo; Dora Reglodi; Gabor K. Toth (Journal of Molecular Neuroscience, 2021)
PACAP is a neuropeptide with widespread distribution and diverse biological functions. It has strong cytoprotective effects mediated mainly through specific PAC1 receptors. Experimental data show protective effects of PACAP in the retina and cornea in several pathological conditions. Although intravitreal injections are a common practice in some ocular diseases, delivery of therapeutic agents in the form of eye drops would be more convenient and would lead to fewer side effects. We have previously shown that PACAP, in the form of eye drops, is able to pass through the ocular barriers and can exert retinoprotective effects. As eye drops represent a promising form of administration of PACAP in ocular diseases, it is important to investigate the stability of PACAP in solutions used in eye drops. In this study, the stability of PACAP1-27 and PACAP1-38 in eye drops was measured in four common media and a commercially available artificial tear solution at both room temperature and +4 °C. Mass spectrometry results show that the highest stability was gained with PACAP1-38 in water and 0.9% saline solution at +4 °C, representing 80–90% drug persistence after 2 weeks. PACAP1-38 in the artificial tear showed very fast degradation at room temperature, but was stable at +4 °C. In summary, PACAP1-38 has higher stability than PACAP1-27, with highest stability at +4 °C in water solution, but both peptides in each medium can be stored for relatively longer periods without significant degradation. These data can provide reference for future therapeutic use of PACAP in eye drops.

Retinoprotective Effects of TAT-Bound Vasoactive Intestinal Peptide and Pituitary Adenylate Cyclase Activating Polypeptide - Tamas Atlasz; D. Werling; S. Song; E. Szabo; A. Vaczy; P. Kovari; A. Tamas; D. Reglodi; Rongjie Yu (Journal of Molecular Neuroscience, 2019)

PACAP deficiency as a model of aging - D. Reglodi; T. Atlasz; E. Szabo; A. Jungling; A. Tamas; T. Juhasz; B. D. Fulop; A. Bardosi (GeroScience, 2018)

The Protective Role of PAC1-Receptor Agonist Maxadilan in BCCAO-Induced Retinal Degeneration - A. Vaczy; D. Reglodi; T. Somoskeoy; K. Kovacs; E. Lokos; E. Szabo; A. Tamas; T. Atlasz (Journal of Molecular Neuroscience, 2016)

PACAP Is Protective in a Rat Model of Retinopathy of Prematurity - Timea Kvarik; Barbara Mammel; Dora Reglodi; Krisztina Kovacs; Dora Werling; Brigitta Bede; Alexandra Vaczy; Eszter Fabian; Gabor Toth; Peter Kiss; Andrea Tamas; Tibor Ertl; et al. (Journal of Molecular Neuroscience, 2016)

PACAP is an Endogenous Protective Factor—Insights from PACAP-Deficient Mice - D. Reglodi; P. Kiss; K. Szabadfi; T. Atlasz; R. Gabriel; G. Horvath; P. Szakaly; B. Sandor; A. Lubics; E. Laszlo; J. Farkas; A. Matkovits; et al. (Journal of Molecular Neuroscience, 2012)

Comparative Examination of Inner Ear in Wild Type and Pituitary Adenylate Cyclase Activating Polypeptide (PACAP)-Deficient Mice - A. Tamas; K. Szabadfi; A. Nemeth; B. Fulop; P. Kiss; T. Atlasz; R. Gabriel; H. Hashimoto; A. Baba; N. Shintani; Zs. Helyes; D. Reglodi (Neurotoxicity Research, 2012)

Protective effects of the neuropeptide PACAP in diabetic retinopathy - Krisztina Szabadfi; Tamas Atlasz; Peter Kiss; Dora Reglodi; Aliz Szabo; Krisztina Kovacs; Balint Szalontai; Gyorgy Setalo; Eszter Banki; Katalin Csanaky; Andrea Tamas; Robert Gabriel (Cell and Tissue Research, 2012)

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Pituitary Adenylate Cyclase-Activating Polypeptide is Protective Against Oxidative Stress in Human Retinal Pigment Epithelial Cells - Laszlo Mester; Krisztina Kovacs; Boglarka Racz; Izabella Solti; Tamas Atlasz; Krisztina Szabadfi; Andrea Tamas; Dora Reglodi (Journal of Molecular Neuroscience, 2011)

PACAP Improves Functional Outcome in Excitotoxic Retinal Lesion: An Electroretinographic Study - Balazs Varga; Krisztina Szabadfi; Peter Kiss; Eszter Fabian; Andrea Tamas; Monika Griecs; Robert Gabriel; Dora Reglodi; Adam Kemeny-Beke; Zsuzsanna Pamer; Zsolt Biro; Arpad Tosaki; et al. (Journal of Molecular Neuroscience, 2011)

Effects of PACAP in UV-A Radiation-Induced Retinal Degeneration Models in Rats - Tamas Atlasz; Krisztina Szabadfi; Peter Kiss; Zsuzsanna Marton; Monika Griecs; Levente Hamza; Valeria Gaal; Zsolt Biro; Andrea Tamas; Gabor Hild; Miklos Nyitrai; Gabor Toth; et al. (Journal of Molecular Neuroscience, 2011)

Protection Against Chronic Hypoperfusion-Induced Retinal Neurodegeneration by PARP Inhibition via Activation of PI-3-kinase Akt Pathway and Suppression of JNK and p38 MAP Kinases - Laszlo Mester; Aliz Szabo; Tamas Atlasz; Krisztina Szabadfi; Dora Reglodi; Peter Kiss; Boglarka Racz; Andrea Tamas; Ferenc Gallyas; Balazs Sumegi; Eniko Hocsak; Robert Gabriel; et al. (Neurotoxicity Research, 2009)

PACAP-Mediated Neuroprotection of Neurochemically Identified Cell Types in MSG-Induced Retinal Degeneration - Tamas Atlasz; Krisztina Szabadfi; Peter Kiss; Norbert Babai; Zsombor Koszegi; Andrea Tamas; Dora Reglodi; Robert Gabriel (Journal of Molecular Neuroscience, 2008)

Diazoxide is protective in the rat retina against ischemic injury induced by bilateral carotid occlusion and glutamate-induced degeneration - T. Atlasz; N. Babai; D. Reglodi; P. Kiss; A. Tamas; F. Bari; F. Domoki; R. Gabriel (Neurotoxicity Research, 2007)